Targeting aberrant replication and DNA repair events for treating breast cancers - Subapriya Rajamanickam; Jun Hyoung Park; Panneerdoss Subbarayalu; Santosh Timilsina; Kaitlyn Bates; Pooja Yadav; Saif S. R. Nirzhor; Vijay Eedunuri; Tabrez A. Mohammad; Kwang Hwa Jung; Benjamin Onyeagucha; Nourhan Abdelfattah; et al. (Communications Biology, 2022)
A report of the small molecule Carbazole Blue demonstrates inhibition of breast cancer growth and metastasis without adverse effects on normal tissue.